Perbedaan Persepsi Konsumen Terhadap Kegunaan dan Kemudahan Dari Situs Website dan Aplikasi Seluler Marriott Group - Pange, Jessceline Eugenia; Nugroho, Agustinus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
As technology develops, big brand hotel companies such as the Marriott Group have created their own websites and mobile applications to facilitate customer reservations. This study aims to explore the differences in perceived usefulness and perceived ease of use between Marriott’s application and website. Using a descriptive quantitative approach, data were collected and analyzed to examine the relationship between variables. The sample comprised 200 Indonesian individuals who had made a reservation on either platform. Data were analyzed using SPSS with a comparison test to evaluate the hypotheses. The results indicate differences in user ease of access, navigation, and consistency of experience and information across platforms. While overall perceptions of usefulness and ease of use were similar, notable differences suggest the importance of focusing on these aspects in the development of Marriott's digital platforms to enhance User Experience.